Simple sentences in children literature, stylistic effects, and unconventional storyline analysis on the latke who couldn’t stop screaming by Lemony Snicket. - Tan, Yong Jian - Jerome (2024)
This study investigates the relationship between simple sentence structures, stylistic effects, and unconventional storyline in children's literature, with a particular emphasis on Lemony Snicket's "The Latke Who Couldn't Stop Screaming." Despite the interest in stylistic syntactic theory and its implications for literary analysis, there is still a significant gap in the study of unconventional children's literature stories and the impact of stylistic effects on children's emotional and cognitive growth. Using the theoretical frameworks of stylistic syntax theory and reader response theory, this research attempts to fill these gaps by analysing the emotional engagement and cognitive stimulation evoked by stylistic devices in Snicket's narrative. The objectives of this research are, to identify the impact of simple sentence structures on the use of stylistic devices in "The Latke Who Couldn't Stop Screaming,". Second, to investigate the contribution of stylistic syntax to the overall emotional impact of the selected short story, with a focus on reader responses and interpretive strategies. Thirdly, determine emotional impact of unconventional children’s literature. This study seeks to shed light on the importance of stylistic effects in children's books and their potential function in shaping readers' emotional responses, cognitive processes, and literary interpretations through a comprehensive examination of Snicket's work.